Is it true that Flash Sale and Free Shipping Tagline Affect Impulsive Buying Behavior of Lazada E-Commerce Users Living in Semarang? (Study on Lazada Marketplace Users in Semarang City) - Salsabila Hasna Kamilah; Erfiyanti; Anita Nurmaida Putri; Khairani Zikrinawati; Zulfa Fahmy (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to determine the effect of flash sales tagline “free shipping on the impulsive buying behavior of Lazada e-commerce users who live in Semarang. The subject of this research is the Lazada application users who live in Semarang who were taken by purposive sampling technique. The measuring instrument in this study was an impulsive buying scale and a questionnaire regarding flash sales and the tagline